Is China Making Africa’s Lunch Or Eating It? An In-depth Analysis Of China’s Trade And FDI In Sub Saharan Africa - Mohammed, Salisu (2012)
Over the past decade or so, economic relations between China and African countries have assumed a quantum leap forward resulting in increased Chinese trade and capital flows to Africa. As a result, China has now overtaken the UK as Africa’s third largest investor, after the US and France. Across the continent, China has invested heavily in multifarious operations and has thus become an influential investor, contractor, builder and donor. Opinion is, however, divided on the potential benefits of China’s engagement with Africa. On the one hand, opponents of Sino-Africa relations argue that Chinese operations in Africa is detrimental to the long-term interests of countries in the region because the overarching objective of the Chinese is to exploit Africa’s natural resources to power their industrialisation agenda, and hence the bulk of their investment is in the oil and mining sectors which have little or no backward and forward linkages with the rest of the African economies. On the other hand, proponents point to the significant growth in Africa’s trade, easy access to international finance, and a wide range of infrastructure developments as visible evidence of some of the benefits of the Sino-Africa relations. This dissertation is motivated by the debates on both sides of the spectrum and decided to investigate the impact of the Chinese trade and investments in Sub-Saharan African countries, with special focus on the eight largest recipients of trade and capital flows from China. The study employed a standard econometric analysis to estimate the coefficients of Chinese trade and foreign direct investment inflows in the economic growth and per capita equations in these countries over the period 2004-2010. The results from the regression analysis show that, with the exception of Gabon, Chinese FDI in the sample of the 8 SSA countries appears to have no discernible effect on economic growth and development. However, the results provide evidence to support the hypothesis that African exports to China play an important role in the economic development process, as the estimated coefficient of the exports is positive and statistically significant. Thus, the results can be said to provide support to both sides of the argument, as while there is insufficient evidence to support the FDI hypothesis, the results appear to lend credence to the exports-growth hypothesis. A number of policy recommendations have been offered to help SSA countries take full advantage of the opportunities, as well as to mitigate the potential risks, arising from the China-Africa relations.